Problem behaviours and psychotropic medication use in intellectual disability: a multinational cross‐sectional survey. Issue 2 (19th January 2018) - Perry, B. I.; Cooray, S. E.; Mendis, J.; Purandare, K.; Wijeratne, A.; Manjubhashini, S.; Dasari, M.; Esan, F.; Gunaratna, I.; Naseem, R. A.; Hoare, S.; Chester, V.; et al.
Abstract: Background: Problem behaviours (PBs) are a common cause for clinician contact in people with disorders of intellectual development and may be a common cause for the prescription of psychotropic medication. We aimed to use a large, multinational sample to define the prevalence of PBs, the associations with psychotropic medication use, and to assess for any potential 'diagnostic overshadowing' by the label of PBs in a population of people with disorders of intellectual development. Method: A multinational, multi‐setting, cross‐sectional service evaluation and baseline audit was completed. Data were collected from UK hospitals, UK community settings, Sri Lanka and Hong Kong. A semi‐structured questionnaire was completed by treating clinicians, capturing demographic details, prevalence rates of intellectual disability and psychotropic medication use, alongside psychiatric co‐morbidity. Results: A sample size of 358 was obtained, with 65% of included participants treated in an inpatient setting. Psychotropic use was prevalent (90%) in our sample, particularly antipsychotics (74%). The prevalence of PB was high (83%). There was no statistically significant association between psychotropic prescription and recorded psychiatric co‐morbidity, suggesting prevalent 'off‐label' use for PBs, or poor recording of psychiatric co‐morbidity. There was some evidence of possible diagnostic overshadowing due to the PB classification. A higher dose of psychotropic medication was associated with aggression toward others ( P = 0.03). Conclusions: We found evidence of prevalent potential 'off‐label' use for psychotropic medication, which may be due to PBs. We also found evidence of potential diagnostic‐overshadowing, where symptoms of psychiatric co‐morbidity may have been attributed to PBs. Our findings provide renewed importance, across borders and health systems, for clinicians to consider a holistic approach to treating PBs, and attempting to best understand the precipitants and predisposing factors before psychotropic prescribing. Highlights: Our cross‐sectional survey is multinational and multi‐setting in scope; We found evidence of potential prevalent 'off‐label' use for psychotropic medication, possibly for use in the treatment of problem behaviours; and We found evidence of potential diagnostic‐overshadowing, where symptoms of psychiatric co‐morbidity may have been attributed to problem behaviours.